Pembangunan Aplikasi Permainan Mudah Alih 2D Kesultanan Johor-Riau Berasaskan Genre Strategi: TD Kota Johor Lama - Nur Zahrah Mohd Zain; Norhalina Senan (Applied Information Technology And Computer Science, 2025)
The Sultanate of Johor-Riau is one of the crucial historical events for Malaysians. So far, reading is the traditional method used to access its context. However, it remains underutilized in technology, specifically mobile game applications. The existing mobile games do not integrate Malaysian local history with strategy gameplay. Thus, this study aims to develop a 2-dimensional (2D) mobile game application called "TD Kota Johor Lama" that showcases the sultanate’s history using tower defense (TD) gameplay. The game is aimed at users aged 13 to 17. It has four levels that adapt the history of the sultanate’s wars. The Unity game engine is used to develop the game, while the methodology is the Game Development Life Cycle (GDLC). Based on the beta testing conducted using the System Usability Scale (SUS) Standard Version, this application is considered acceptable, scoring 70.5%, proving the application has been successfully built and users can accept it.